2019
DOI: 10.4049/jimmunol.1800747
|View full text |Cite
|
Sign up to set email alerts
|

Online Hemodiafiltration Inhibits Inflammation-Related Endothelial Dysfunction and Vascular Calcification of Uremic Patients Modulating miR-223 Expression in Plasma Extracellular Vesicles

Abstract: Decreased inflammation and cardiovascular mortality are evident in patients with end-stage chronic kidney disease treated by online hemodiafiltration. Extracellular vesicles (EV) are mediators of cell-to-cell communication and contain different RNA types. This study investigated whether mixed online hemodiafiltration (mOL-HDF) beneficial effects associate with changes in the RNA content of plasma EV in chronic kidney disease patients. Thirty bicarbonate hemodialysis (BHD) patients were randomized 1:1 to contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 49 publications
(57 reference statements)
2
61
0
Order By: Relevance
“…miR-130a target(s) validation. Transfection of mimic-miR-130a (10 nM) was performed on ECs using HiPerfect Transfection method (Qiagen, Valencia, USA) 63 . Total RNA from untreated ECs, ECs transfected with mimic-miR-130a, treated with sEV with high (D17, D18, D20) or low miR-130a content (D1, D2, D4) was extracted using All-in-One Purification kit (Norgen, Thorold, ON Canada).…”
Section: Pathways and Mir Target Prediction Analysis Of Ev Content Tmentioning
confidence: 99%
See 2 more Smart Citations
“…miR-130a target(s) validation. Transfection of mimic-miR-130a (10 nM) was performed on ECs using HiPerfect Transfection method (Qiagen, Valencia, USA) 63 . Total RNA from untreated ECs, ECs transfected with mimic-miR-130a, treated with sEV with high (D17, D18, D20) or low miR-130a content (D1, D2, D4) was extracted using All-in-One Purification kit (Norgen, Thorold, ON Canada).…”
Section: Pathways and Mir Target Prediction Analysis Of Ev Content Tmentioning
confidence: 99%
“…miR-Scramble (Scr) was used as transfection reference sample. The expression of miR-130a was evaluated by RT-PCR 63 . miR-130a targets were analyzed by Western Blot analysis.…”
Section: Pathways and Mir Target Prediction Analysis Of Ev Content Tmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Pickering et al reported that serum miR-26a, miR-34a, and miR-223 did not differ between those with and without VC progression [77], findings that are in contrast to those by Cavallari et al, who described that plasma miR-223 increased in those with ESRD under chronic dialysis [49]. It is likely that the numbers of subjects being tested, the timing of the assay for circulatory miRNAs, the controls used to derive miRNA data, and the biologic fluid assayed may account for the discrepancy we observed.…”
Section: Discrepancies Between Calcified and Non-calcified Tissues Ormentioning
confidence: 81%
“…Alternatively, VSMCs with miR-223 over-expression had increased proliferation and migratory ability, while calcified VSMCs had significantly up-regulated miR-223 levels [18]. Cavallari et al also showed that uremic patients with VC had nearly 2-fold higher levels of plasma exosomal miR-223 compared to control groups [49], lending support to the potential agonistic effect for VC for miR-223. This difference in miR-223 effect on VC seems to depend on cell type and the clinical context being evaluated.…”
Section: Mirnas With Controversial Influences On Vcmentioning
confidence: 98%